Inhibitory and Agonistic Autoantibodies Directed Against the β2-Adrenergic Receptor in Pseudoexfoliation Syndrome and Glaucoma - Hohberger, Bettina; Schlötzer-Schrehard, Ursula; Mardin, Christian; Lämmer, Robert; Munoz, Luis; Kunze, Rudolf; Herrmann, Martin; Wallukat, Gerd (Frontiers in Neuroscience, 2021)
Pseudoexfoliation syndrome (PEXS) and glaucoma (PEXG) are assumed to be caused by a generalized elastosis leading to the accumulation of PEX material in ocular as well as in extraocular tissues. The exact pathophysiology of PEXS is still elusive. PEXG, the most common type of secondary open-angle glaucoma (OAG), is characterized by large peaks of intraocular pressure (IOP) with a progressive loss of the visual field. Agonistic autoantibodies (agAAb) against the ß2 adrenergic receptor (AR) have been shown to be present in sera of patients with primary and secondary OAG and ocular hypertension (OHT) and are seemingly linked to IOP. In the present study we investigated the autoantibodies directed against the ß2-AR in sera of patients with PEXS and PEXG. We recruited 15, 10 and 15 patients with PEXG, PEXS, and primary OAG, respectively. Ten healthy individuals served as controls. All patients underwent standard ophthalmological examination with Octopus G1 perimetry. agAAb prepared from serum samples were analyzed in a rat cardiomyocyte-based bioassay for the presence of agAAb. We identified the interacting loop of the ß2-AR and the IgG subclasses using synthetic peptides corresponding to the extracellular loops of the receptors and ELISA, respectively. None of the controls were ß2-agAAb positive (0.2±0.5 U). No ß2-agAAb (0.2±0.4 U), but inhibitory ß2-AAb were observed in 80% of the patients that partially blocked the drug-induced β2-adrenergic stimulation; 5.8±1.7 U versus 11.1±0.9 U for clenbuterol in the absence and the presence of sera from patients with PEXS, respectively. Epitope analyses identified the 3rd extracellular loop of the β2-AR as the target of the inhibitory ß2-AAb, being of IgG3 subtype in PEXS patients. In contrast, patients with PEXG showed ß2-agAAb (5.6±0.9 U), but no inhibitory ones. The ß2-agAAb levels of patients with PEXG and POAG patients (3.9±2.8 U; p>0.05) were at a similar level. In 2 cases of PEXG the ß2-agAAb exert synergistic effects with clenbuterol. The activity increased from 11.5±0.3 (clenbuterol only) to 16.3±0.9 U. As autoimmune mechanisms were reportedly involved in the pathogenesis of glaucoma; agonistic and inhibitory ß2-AAb seem to be a part of this multifactorial interplay.